LEGAL PROTECTION FOR WOMEN WORKERS IN INDONESIA: A CRITICAL REVIEW OF LAW APPLICATION - Prasetyo, Dedy Ardian (Faculty of Law, Universitas Pekalongan, 2024)
When compared to their male counterparts, female workers frequently experience discrimination in labor rights concerns pertaining to their protection, particularly in areas of reproductive function, pay, and positions. The purpose of this study is to examine the laws intended to safeguard Indonesian women workers' rights. Normative legal research is the methodology used in this investigation. Law Number 6 of 2023 Article 153 and Regulation of the Minister of Women's Empowerment and Child Protection Number 1 of 2023 are the main sources of data for this study. According to the study's findings, women workers have not yet received the best protection possible under Law No. 6 of 2023 and the Ministerial Regulation of PA No. 1 of 2023. The requirement for workers to learn more about the relevant legislation is the reason for the low implementation of these policies. According to the same report, a large number of female employees need to be aware of the laws obliging businesses to offer maternity leave. Furthermore, the provision of shelter houses for female employees in the workplace is governed by the Ministerial Regulation of PPPA No. 1 of 2023. Only 72 businesses will be dedicated to offering RP3 across Indonesia in 2023. DKI Jakarta, Bogor, Bekasi, Subang, Riau Islands, South Sumatra, Banten, and East Java are among the regions that have adopted RP3. Despite the implementation of Law No. 6 of 2023 and Ministerial Regulation No. 1 of 2023, not all Indonesian women workers are aware of or able to utilize their current protection rights.